2000
DOI: 10.1111/j.0435-3676.2000.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and origin of upland block fields on melville peninsula, eastern canadian arctic

Abstract: Block fields have developed on gently graded uplands of granite and gneiss on central and southern Melville Peninsula. The location of block fields is not controlled by elevation, but rather by areas covered by cold-based ice during the last glaciation. Block fields consist either of angular boulders, sorted circles 3-4 m across having blocky rims and central areas of weathered grus, concentrations of openwork boulders, or in the southeast, of immature bouldery till. The block fields are primarily relict featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Percentages of clay are low in all samples at both sites, ranging from 3% to 6%, with only BG-06-04 exceeding 10%. Such percentages of clay are at the low end of the range previously reported for blockfields (4-25%; Caine 1968; Rea et al 1996a, b;Dredge 2000;Marquette et al 2004;Paasche et al 2006). SEM images of surface fine matrix (BG-06-09 and BG-06-22 in Table 1) revealed the presence only of primary minerals that occur in local bedrock, including amphibole, albite, chlorite and minor amounts of anorthite and K-feldspar (Fig.…”
Section: Fine Matrix Granulometry and Semmentioning
confidence: 56%
See 1 more Smart Citation
“…Percentages of clay are low in all samples at both sites, ranging from 3% to 6%, with only BG-06-04 exceeding 10%. Such percentages of clay are at the low end of the range previously reported for blockfields (4-25%; Caine 1968; Rea et al 1996a, b;Dredge 2000;Marquette et al 2004;Paasche et al 2006). SEM images of surface fine matrix (BG-06-09 and BG-06-22 in Table 1) revealed the presence only of primary minerals that occur in local bedrock, including amphibole, albite, chlorite and minor amounts of anorthite and K-feldspar (Fig.…”
Section: Fine Matrix Granulometry and Semmentioning
confidence: 56%
“…This article concerns the weathering and origin of an autochthonous blockfield in the northern Swedish mountains. Autochthonous blockfields are coarse, blocky mantles produced by in situ weathering, and occur in many periglaciated landscapes (Dahl 1966;Ives 1966;Caine 1968;Clapperton 1975;Clark & Ciolkosz 1988;Nesje et al 1988;Kleman & Borgstr¨om 1990;Ballantyne 1998;Dredge 2000;Boelhouwers 2004;Sumner & Meiklejohn 2004;Firpo et al 2006;Goodfellow 2007). In formerly glaciated settings, autochthonous blockfields frequently indicate surfaces that have not been significantly modified by glacial processes, because they either protruded as nunataks above surrounding ice sheets or were protected by cold-based ice covers (Ives 1958;Sugden & Watts 1977;Nesje 1989;Kleman & Borgstr¨om 1990;Ballantyne et al 1998;H¨attestrand & Stroeven 2002;Marquette et al 2004;Fjellanger et al 2006).…”
mentioning
confidence: 99%
“…On the other hand, the beds of former ice sheets are accessible and reveal a picture of highly dynamic behavior of past ice sheets. For example, the reconstruction of low-gradient outlet glaciers (e.g., Clark, 1994;Patterson, 1998), ice streaming (e.g., Clark, 2001, 2002;Boulton et al, 2001;Kaplan et al, 2001), and frozen-bedded conditions (e.g., Dyke, 1993;Kleman, 1994;Dredge, 2000;Kleman and Hättestrand, 1999) in formerly glaciated regions, along with widespread ice-rafted debris in adjacent ocean basins (e.g., Bond et al, 1992;Andrews and Tedesco, 1992;Andrews et al, 1998) point toward Pleistocene ice sheets that have all the dynamic components of their modern-day counterparts. These reconstructions also add a longer-term perspective on contemporary ice-sheet dynamics, allowing for the rates and time scales of various processes to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the variation in the LIS ice fl ow record was thought to have occurred during the last glacial cycle, and its discovery led to three important conclusions: (1) LIS domes that persisted throughout the last glacial cycle were not only deglacial phenomena, but existed and shifted their location throughout the last glacial cycle, (2) the shifting of domes was likely related to ice stream activity (e.g., Stokes and Clark, 2001;Jansson et al, 2003), and (3) in some places erosion was not substantial enough to remove prior bedforms, indicating minimal glacial erosion and landscape preservation near ice sheet centers (Kleman and Hättestrand, 1999). Several studies showed that large portions of former ice sheets were frozen to the bed and preserved ancient (preglacial) terrain upon deglaciation (e.g., Shilts et al, 1979;Dyke, 1993;Kleman, 1994;Dredge, 2000).…”
Section: Laurentide Ice Sheet Backgroundmentioning
confidence: 99%
“…An added complication in many sectors of the LIS is the realization that cold-based ice can lead to the preservation of preglacial organic-rich surfi cial sediments (Davis et al, in press). It is becoming increasingly clear that while some areas beneath the LIS experienced intense erosion, some landscapes were only slightly modifi ed during the last glacial cycle (e.g., Kleman and Hättestrand, 1999;Bierman et al, 2000;Dredge, 2000;Colgan et al, 2002;Jansson et al, 2003;Briner et al, 2003;Marquette et al, 2004;Staiger et al, 2005), complicating the interpretation of stratigraphic and geomorphic records of the last glaciation.…”
Section: Introductionmentioning
confidence: 99%